Chronic Inflammatory Gingival Enlargement Managed by Scaling and Root Planing with Curettage: A Case Report - Abhaya Chandra Das1, Sourav Panda1, Manoj Kumar1, Rinkee Mohanty2, Rashmita Nayak2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Gingival enlargement (GE) is defined as an increase in the size of the gingiva. It is also known as gingivalovergrowth. A wide variety of etiological factors play an important role in the development of GE. GE maybe acute or chronic. However chronic inflammatory GE is most commonly found. Prolonged exposureof dental plaque is the most common etiological factor of chronic GE. A 23-year-old girl came to theDepartment of Periodontics, with a chief complaint of swelling of gums in lower front teeth regions. Onclinical examination, there was grade II GE in 33 to 43 regions along with the presence of calculus in thelingual side, and poor oral hygiene too. It was planned for phase I therapy followed by phase II therapy.So scaling and root planing was performed and after 4 weeks curettage was done under infiltration localanesthesia. The subject was instructed to maintain oral hygiene. After 2 months, it was found completeresolution of GE. She was very satisfied with the result.